2017
DOI: 10.1016/j.gene.2016.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Structure, biochemistry, and biology of PAK kinases

Abstract: PAKs, p21-activated kinases, play central roles and act as converging junctions for discrete signals elicited on the cell surface and for a number of intracellular signaling cascades. PAKs phosphorylate a vast number of substrates and act by remodeling cytoskeleton, employing scaffolding, and relocating to distinct subcellular compartments. PAKs affect wide range of processes that are crucial to the cell from regulation of cell motility, survival, redox, metabolism, cell cycle, proliferation, transformation, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
201
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(208 citation statements)
references
References 246 publications
(245 reference statements)
4
201
2
1
Order By: Relevance
“…The p21‐activated kinases (PAKs) are a class of conserved serine/threonine protein kinases that are considered modulators of cell cycle progression, gene transcription, cell motility and cell transformation. Six mammalian PAKs have been identified, and they can be categorized into two subgroups, Group I (PAK1–3) and Group II (PAK4–6), based on sequence and structure . Studies indicate that p21‐activated kinase 5 (PAK5), the most recently identified member of the PAK family, plays an indispensable role in regulation of the cytoskeleton, microtubule stability and cell survival .…”
Section: Introductionmentioning
confidence: 99%
“…The p21‐activated kinases (PAKs) are a class of conserved serine/threonine protein kinases that are considered modulators of cell cycle progression, gene transcription, cell motility and cell transformation. Six mammalian PAKs have been identified, and they can be categorized into two subgroups, Group I (PAK1–3) and Group II (PAK4–6), based on sequence and structure . Studies indicate that p21‐activated kinase 5 (PAK5), the most recently identified member of the PAK family, plays an indispensable role in regulation of the cytoskeleton, microtubule stability and cell survival .…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, PAK proteins are encoded by six genes (PAK 1-6) and are subdivided into two groups (group I, PAK 1-3; group II, PAK 4-6). PAK proteins are known to affect many biological processes, including cell cycle, proliferation and survival (Kumar et al, 2017). PAK proteins are known to affect many biological processes, including cell cycle, proliferation and survival (Kumar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The p21‐activated kinase (PAK) family has six members, PAK1‐6, which function as key effectors of RHO family GTPases in mammalian cells to regulate several pathways including Ras/Raf/MEK/ERK, Wnt/β‐catenin, and likely others that have yet to be identified . PAKs are subdivided into two groups, type I (PAK1, PAK2, and PAK3) and type II (PAK4, PAK5, and PAK6); while all PAKs are involved in common signaling pathways, group I and II have different modes of regulation, different tissue distributions, and both common and unique substrates . All PAK proteins have been linked in some regard to cancers, but only PAK3 has thus far been linked to a developmental condition; variants in PAK3 cause an X‐linked form of intellectual disability (OMIM 300558) .…”
Section: Introductionmentioning
confidence: 99%
“…PAKs are subdivided into two groups, type I (PAK1, PAK2, and PAK3) and type II (PAK4, PAK5, and PAK6); while all PAKs are involved in common signaling pathways, group I and II have different modes of regulation, different tissue distributions, and both common and unique substrates . All PAK proteins have been linked in some regard to cancers, but only PAK3 has thus far been linked to a developmental condition; variants in PAK3 cause an X‐linked form of intellectual disability (OMIM 300558) . Overall, it is clear the PAK family has many essential roles and we are just beginning to realize their significant impact when dysregulated.…”
Section: Introductionmentioning
confidence: 99%